Update on Outcome Measure Development in Large-vessel Vasculitis: Report from OMERACT 2018 - ALİBAZ ÖNER, FATMA; DİRESKENELİ, RAFİ HANER (J RHEUMATOL PUBL CO, 2019)
Objective. The Outcome Measures in Rheumatology (OMERACT) Vasculitis Working Group seeks to develop validated outcome measures for use in trials for large-vessel vasculitis (LVV). Methods. An international Delphi exercise conducted among investigators identified items considered important to measure active disease. In parallel, qualitative research with patients was conducted, including interviews and focus groups. Results. Next steps prioritized by the group for LVV include (1) defining disease states (remission, flare, and patient-acceptable symptom state) and (2) selection of patient-reported outcome tools. Conclusion. The ultimate goal is to develop an OMERACT-endorsed core set of outcome measures for use in clinical trials of LVV.
Keywords: VASCULITIS; TAKAYASU ARTERITIS; GIANT CELL ARTERITIS; LARGE-VESSEL VASCULITIS; OUTCOMES; OMERACT; QUALITY-OF-LIFE; GIANT-CELL ARTERITIS; DISEASE-ACTIVITY; TAKAYASUS-ARTERITIS; ACTIVITY SCORE; HEALTH